Regional Economic Outlook, November 2018, Middle East and Central Asia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2018)
As in other regions in the world, countries in MENAP and CCA regions are exposed to tightening in global financing conditions and ongoing global trade tensions. The former has already begun to impact several emerging market economies in MENAP and could have more severe implications should financial market sentiment suddenly deteriorate. Escalating global trade tensions will have a limited direct and immediate impact on these regions but could impart significant strains over time through negative effects on trading partners and through market confidence effects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet